1981
DOI: 10.1136/gut.22.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of endoscopic argon laser photocoagulation in bleeding peptic ulcers.

Abstract: SUMMARY Emergency endoscopy on 332 patients with acute upper gastrointestinal bleeding showed that 178 had peptic ulcers; 28 of these were actively bleeding (spurting) and 108 showed stigmata of recent haemorrhage (vessels or spots in the ulcer base) suggesting a risk of rebleeding. These 136 patients were randomly allocated to Argon laser photocoagulation or to no additional therapy (controls) at the time of initial endoscopy. All patients received conventional management, and the controlling clinicians did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(30 citation statements)
references
References 16 publications
2
26
0
2
Order By: Relevance
“…The decade from the early 1970s saw the rapid development of a host of endoscopically based treatments, including the management of oesophageal obstruction, foreign bodies and acute gastrointestinal bleeding. 10,11 Colonoscopic polypectomy was truly a breakthrough in colorectal medicine. 12 Therapeutic ERCP revolutionised the management of biliary obstruction, with the introduction of biliary sphincterotomy for removal of stones 13 and the use of plastic stents to relieve jaundice.…”
Section: Therapeutic Endoscopymentioning
confidence: 99%
“…The decade from the early 1970s saw the rapid development of a host of endoscopically based treatments, including the management of oesophageal obstruction, foreign bodies and acute gastrointestinal bleeding. 10,11 Colonoscopic polypectomy was truly a breakthrough in colorectal medicine. 12 Therapeutic ERCP revolutionised the management of biliary obstruction, with the introduction of biliary sphincterotomy for removal of stones 13 and the use of plastic stents to relieve jaundice.…”
Section: Therapeutic Endoscopymentioning
confidence: 99%
“…The fiber should be kept at a distance of 1-3 cm from the bleeding point. Swain et al [21,22] have shown a significant reduction in the need for emergency surgery and mortality from Nd-YAG and argon laser treatment in two separate studies, while Rutgeerts et al [23] and Krejs et al [24] using the Nd-YAG and Vallon et al [25] using the argon laser did not report any difference in these end point variables. However, in these studies, there was a significant percentage of patients who were excluded due to inaccessibility of the lesion for the laser beam and equipment failure, which are the main drawbacks for laser therapy.…”
Section: Hemostatic Modalitiesmentioning
confidence: 96%
“…The first argon laser trial was reported by Vallon et al [15] in 1981. 136 patients with bleeding peptic ulcers were divided into three groups and randomized to laser therapy or control.…”
Section: Macleod [Pers Commun] Nd:yag 12mentioning
confidence: 99%
“…Vallon et al [ 15] argon 136 Swain et al [16] argon 76 Jensen et al [ 17] argon 12 VV = Visible vessel; NR nically impossible.…”
Section: Macleod [Pers Commun] Nd:yag 12mentioning
confidence: 99%